KETAHANAN PANGAN RUMAH TANGGA MELALUI PEMANFAATAN TAMAN RUMAH DENGAN BUDIDAYA SAYURAN DI MASA ADAPTASI BARU PANDEMI COVID 19 - Syahid - Syahid; Nurdeni - Nurdeni; Sri - Mardiyati; Dian Novita Susanto (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
Food security is a condition for the fulfillment of food needs for each household, namely, from sufficient food availability with maintained quality as well as being economical. Household gardens as one of the nearest sources to produce sources of household food security in fulfillment of the needs of household nutrition and also to reduce household expenditure as well as increase household income. The aim of this PKM (Community Services) activity is to escalate housewives’ capability in managing the household gardens and also provide insight, knowledge as well as transferred expertise in the cultivation of vegetable crops in limited spaces. This method is carried out through counseling, discussion, as well as simulation so that they can be practiced at their homes. The results from this PKM activity are to create the cultivation of healthy vegetable crops that are rich in nutrition in every household at Vinus housing Desa Sayang Kecamatan Jatinangor Kabupaten Sumedang Jawa Barat.